1998
DOI: 10.1161/01.hyp.31.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Control of Sympathetic Nerve Activity in Essential and Secondary Hypertension

Abstract: Abstract-Studies performed in experimental animals and in humans have documented that high blood pressure markedly impairs baroreceptor control of heart rate. Whether a similar impairment also characterizes baroreceptor control of sympathetic activity modulating peripheral vasomotor tone is still unknown. In 28 untreated essential hypertensive subjects [14 of moderate and 14 of more severe degree, age 51.6Ϯ2.4 and 52.6Ϯ2.1 years (meanϮSEM)] and in 13 untreated secondary hypertensives (renovascular or pheochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
341
2
19

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 459 publications
(390 citation statements)
references
References 35 publications
28
341
2
19
Order By: Relevance
“…The resting BRS for tachycardia was lower than that for bradycardia but was within the range of previously reported values in anesthetized rats (4,6). A similar selective impairment of the parasympathetic components of the BRS has been observed in conscious older SD rats (20), in diet-induced obese rats (5), and in human hypertension (17). The lower BRS for bradycardia in older rats was not due to differences in ␣-adrenergic responsiveness, as pressor responses to phenylephrine were similar compared with younger rats.…”
Section: Discussionsupporting
confidence: 88%
“…The resting BRS for tachycardia was lower than that for bradycardia but was within the range of previously reported values in anesthetized rats (4,6). A similar selective impairment of the parasympathetic components of the BRS has been observed in conscious older SD rats (20), in diet-induced obese rats (5), and in human hypertension (17). The lower BRS for bradycardia in older rats was not due to differences in ␣-adrenergic responsiveness, as pressor responses to phenylephrine were similar compared with younger rats.…”
Section: Discussionsupporting
confidence: 88%
“…This is shown in Fig. 2, which refers to the results of a microneurographic study performed by our group in mild and more severe essential hypertensive patients (10). Indeed, when the nerve firing rate, i.e., the number of sympathetic bursts over time or corrected for heart rate, was assessed in normotensive middle-age subjects and in untreated age-matched patients displaying blood pressure elevations of increasing severity, the results showed that not only mild but also more severe essential hypertension was characterized by sympathetic overactivity.…”
Section: Sympathetic Function In Hypertension and In Obesitymentioning
confidence: 84%
“…This is based on the evidence that 1) cardiovascular as well as metabolic function are modulated by sympathetic mechanisms and 2) several of the pathologic states clustering in the metabolic syndrome already display an increased adrenergic drive (2,3,10,(18)(19)(20). This is also based on the finding that when obesity and hypertension are concomitantly present in the same patient, the degree of sympathetic activation is much greater than in patients with either condition singly (24).…”
Section: Sympathetic Overdrive In the Metabolic Syndromementioning
confidence: 99%
“…36 In this study, the baseline values of sympathetic activity in hypertensive subjects were similar to those reported by other authors. 40,41 We showed that 2 months of therapy with simvastatin reduced sympathetic nervous activity.…”
Section: Discussionmentioning
confidence: 97%